The Evolution of Warfare and Weapons in Japan, 792–1392 - Sean O’Reilly (Histories, 2024)
The fearsome Japanese samurai, a legendary figure whose primary attribute was loyalty or honor, needs no introduction. He is strongly associated with the equally famous katana. The popular image of the samurai probably would appear wearing armor but certainly does not carry a shield. This figure, many assume, must have dominated medieval Japan. Yet is this samurai image accurate? Can it withstand sustained scrutiny? What was Japanese warfare really like 1000 years ago? In this article, I evaluate the key sources on medieval warfare in Japan, identifying the contributions of each and pointing out some methodological problems they face. The most prominent casualty of this synthetic analysis is the pop culture image of the heroic and honorable sword-wielding samurai.